In situ visualisation and analysis of dynamic single atom processes in heterogeneous catalysts. Issue 11 (18th November 2021) - Gai, Pratibha L.; Boyes, Edward D.
Abstract : Heterogeneous chemical reactions catalyzed over solid surfaces at operating temperatures are used to produce a vital part of energy, food, healthcare products, cleaner environments and chemicals. Abstract : Heterogeneous chemical reactions catalyzed over solid surfaces at operating temperatures are used to produce a vital part of energy, food, healthcare products, cleaner environments and chemicals. The reactions take place at the atomic level, with active structures forming under dynamic reaction conditions. Therefore, real time in situ visualisation and analysis of gas–solid catalyst reactions under realistic controlled working conditions are crucial to understanding the relation between the dynamic catalyst atomic structure and function for the rational development of improved catalysts and processes. Increasingly, dynamic single atoms and atom clusters are believed to be important in catalytic reactions leading to enhanced catalyst performance. However, dynamic chemical reaction mechanisms at the single atom level under extreme reaction conditions of gas and temperature are not well understood. The novel development of the analytical atomic resolution Environmental (Scanning) Transmission Electron Microscope (E(S)TEM) enables the visualisation and analysis of gas–solid catalyst reactions at the single atom level under controlled reaction conditions of gas environment and temperature. The recent development of the ESTEM advances the capability of the established ETEM, with detection of dynamic single atoms and the associated processes of selected heterogeneous catalysts in their working state. The data provide improved understanding of dynamic single atom processes and reaction mechanisms in heterogeneous catalyst, including the catalytic activity and deactivation at the atomic level and the chemistry underpinning important technological processes. The highlights include platinum/carbon systems of interest in fuel cells to meet energy demands and reduce environmental pollution, and the activation of supported cobalt practical catalysts in Fischer–Tropsch syntheses to produce fuels. Benefits of atomic resolution-E(S)TEM to science and technology include new knowledge of dynamic single atom processes in heterogeneous catalysts and improved processes.